(untitled) (Educação e Pesquisa, 2023)
The purpose of this document is to analyze the results of previous research where the components with the low or null presence of the Didactical Suitability Criteria (DSC) in developed tasks (didactic sequences) for a training course in the teaching of Mathematics are reviewed. Individual semi-structured interviews were conducted with five teachers who participated in the previous research to gather information on why these results were obtained. The interview consisted of eight questions on the component’s connections, didactical innovation, representativeness of complexity, errors, social-professional practicality, and autonomy. The analysis was conducted through a qualitative study of the semantic units of meaning (descriptive analysis). These were extracted from the transcripts of the interviews guided. The results revealed that most interviewees indicated that components, such as autonomy and social-professional practicality, generate positive emotions in their students. It is concluded that the teachers’ reflection on their mathematics classes up to that time was considered a non-priority for the components whose score was low. However, the interviewees considered the importance of modifying their educational practices by employing other components of the DSCs to have quality teaching and learning processes.